MHC class II expression in pancreatic tumors: a link to intratumoral inflammation - Gaida, Matthias; Welsch, Thilo; Herpel, Esther; Tschaharganeh, Darjus-Felix; Fischer, Lars; Schirmacher, Peter; Hänsch, Gertrud Maria; Bergmann, Frank (Virchows Archiv, 2012)
Major histocompatibility complex class II antigens (MHC class II) are constitutively expressed by professional antigen presenting cells and present antigenic peptides to specific CD4+ T lymphocytes. MHC class II expression, however, can also be induced on epithelial cells and in a variety of solid tumors. We tested MHC class II expression on tissue samples derived from patients with pancreatic ductal adenocarcinoma (PDAC) and pancreatic endocrine tumors (PET). Immunohistochemistry revealed MHC class II expression in 86 of 112 (76.8%) PDAC samples and in 30 of 43 (70.0%) PET samples. In PDAC and PET, MHC class II expression correlated significantly with severity and activity of intratumoral inflammation, as well as with the infiltration of CD4+ T lymphocytes. High MHC class II expression significantly correlated with a better histological grade of differentiation in PDAC. In vitro MHC class II expression could be induced on PDAC tumor cell lines by interferon-γ. These cells were then able to present the staphylococci enterotoxin B superantigen to T lymphocytes, which resulted in T cell proliferation. Our findings suggest that MHC class II expression on pancreatic tumor cells is induced by the intratumoral inflammatory reaction in pancreatic tumors.
First online: 27 November 2011
Gesehen am 08.06.2018